Tribal people and their socio-economic characteristics in Rangamati sadar thana - Mullah, Muhammad Abu Shadeque; Parveen, Nabila; Ahshanullah, Mohammad (BRAC University, 2010)
Bangladesh is a densely populated country of South East Asia that has a rich tribal presence. There are about 58 tribes living in different parts of the country. Bangladesh has 1.2 million tribal people, which is just above 1 percent of the total population. Whatever the population they differ in their social organizations, marital customs, rites and rituals, food and other customs from the people of the rest of the country. Most of the tribal people speak in Tibeto-Burman tongues. This paper presents a brief description of the socio-economic characteristics of the Tribal people of Rangamati Sadar Thana on the basis of data collected through a field survey. The survey covered a random sample of 200 households. This paper reveals that the tribal people are lagging behind the mainstream population with respect to economical, political, social and technological standings and still going on with outmoded lifestyle and ideology.